Clinical Profile and Mortality in Children with Pneumonia - Manivel, Ashvinii; Sudarwati, Sri; Herdiningrat, RB. Soeherman (Althea Medical Journal, 2015)
Background: Pneumonia is the leading killer in under-five children. Therefore, by identifying the dangerÂ signs, we are able to predict children who are at higher risk of mortality. The objective of the study is toÂ identify the relationship between the clinical profile and mortality in children with pneumonia at Dr. HasanÂ Sadikin General Hospital, Bandung.Methods: This was an analytical study with a retrospective case control approach using medical recordsÂ with patientâs age limitation of 1â60 month. The study period started on January 1st 2010 and ended onÂ December 31st 2011. All types of pneumonia included whereas congenital anomalies, immunocompromisedÂ and Downâs syndrome patients were excluded in this study. Data were presented as frequency distribution.Results: During the study period, there were 653 children under age of 5 with pneumonia. Only 56 subjectsÂ met the inclusion and exclusion criteria. Twenty-eight patients with pneumonia were cured and 28 died.Â Based on the phiâs coefficient, tachycardia (Î±-value = 0.019) and hepatomegaly (Î±-value = 0.001) wereÂ significant predictors of death and based on the Mantel-Haenszel analysis, hepatomegaly (OR=9.62, CIÂ 95% 2.349â39.35) was significant as a risk for mortality. Inability to drink, cyanosis, tachypnea, grunting,Â vomiting, convulsion, and unconsciousness were not related to mortality.Conclusion: Tachycardia and hepatomegaly have a significant relationship with mortality in under-fiveÂ children with pneumonia. [AMJ.2015;2(1):235â40]